2018
DOI: 10.5599/jese.469
|View full text |Cite
|
Sign up to set email alerts
|

Internal resistance and temperature change during over-discharge of lead-acid battery

Abstract: <p class="PaperAbstract"><span lang="EN-GB">In recent decades, more and more electronic systems (start-stop, drive-by-wire, brake-by-wire) have been developed in the automotive industry therefore reliable power sources are necessary. It is essential to understand thoroughly the detailed behavior of the battery to increase its efficiency, stability and monitorability which is the most popular field nowadays. Over-discharge plays an important role in aging because it increases the probability of init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…This has been performed thoroughly via mathematical modeling [24][25][26], which also included comparisons with other studies. Broda and Inzelt investigated internal resistance increase and temperature change for both the negative and the positive electrode in a lead-acid battery [27]. Křivík dedicated his effort to thermal events in lead storage batteries [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This has been performed thoroughly via mathematical modeling [24][25][26], which also included comparisons with other studies. Broda and Inzelt investigated internal resistance increase and temperature change for both the negative and the positive electrode in a lead-acid battery [27]. Křivík dedicated his effort to thermal events in lead storage batteries [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 28 investigated the over‐discharge behavior of a 2.9 Ah cylindrical Li(Ni 0.8 Co 0.1 Mn 0.1 )O 2 /graphite battery under an adiabatic environment and asserted that a higher over‐discharge rate resulted in a faster temperature rise. Broda and Inzelet 29 conducted experiments to reveal the internal resistance and temperature changing trend during the over‐discharging process of a lead‐acid battery and found that the temperature and internal resistance of the battery increased remarkably under over‐discharging conditions, manifesting severe influences on aging and capacity degradation. Qian et al 30 investigated the cycle life decay behavior of a Li(Ni 1/3 Co 1/3 Mn 1/3 )O 2 /graphite high‐power battery during a slight over‐discharging process and noticed a cycle life degradation of 15.4%.…”
Section: Introductionmentioning
confidence: 99%